Calibrating the PhD for Industry 4.0: global concerns, national agendas and Australian institutional responses. Issue 2 (3rd July 2019) - Molla, Tebeje; Cuthbert, Denise
ABSTRACT: The demands of Industry 4.0 (the Fourth Industrial Revolution) for a future-ready skilled workforce have placed significant political pressure on PhD programs to deliver different sorts of graduates. The paper documents the prevalent 'skills gap' narrative of global policy actors and, and using a multi-scalar policy lens, examines global and national research-training policy debates and Australian institutional responses to calls to transform the PhD to make it more amenable to the new economic conditions. We provide a survey and analysis of recent institutional changes to the PhD in Australia and find that these fall into three overlapping categories: increased employability skills training; the development of industry- and end-user engaged programs; and flexible pathways to the PhD. Following this analysis, we step back to ask some critical questions of these developments both in terms of how effectively they answer the challenges put out in Industry 4.0 discourses and the problematic assumptions, silences and omissions in the policy debates and university responses. Drawing on a capability approach to human development we argue that PhD graduates should not only be prepared to meet the demands of Industry 4.0 but also to lead us through the socio-economic transformations this revolution may entail.